2012
DOI: 10.7150/ijms.4916
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-, But Not Single-, Dose of Parecoxib Reduces Shoulder Pain after Gynecologic Laparoscopy

Abstract: Background: The aim of this study was to investigate effect of single- and multiple-dose of parecoxib on shoulder pain after gynecologic laparoscopy.Methods: 126 patients requiring elective gynecologic laparoscopy were randomly allocated to three groups. Group M (multiple-dose): receiving parecoxib 40mg at 30min before the end of surgery, at 8 and 20hr after surgery, respectively; Group S (single-dose): receiving parecoxib 40mg at 30min before the end of surgery and normal saline at the corresponding time poin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 42 publications
3
12
0
1
Order By: Relevance
“…The data indicated that administration of multi-dose parecoxib (40 mg every 12 h) relieved postoperative pain intensity and incidence, and reduced the requirement for analgesics. These observations are in accordance with results of other studies that indicated that 40 mg parecoxib twice daily ameliorated post- A B C laparoscopic pain, and attenuated the incidence of visceral and shoulder pain with a reduced requirement for analgesics following gynecological laparoscopy (29,30). In contrast to the traditional opioid drugs, parecoxib exerts its analgesic effect without opioid-induced hyperalgesia.…”
Section: A B C Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The data indicated that administration of multi-dose parecoxib (40 mg every 12 h) relieved postoperative pain intensity and incidence, and reduced the requirement for analgesics. These observations are in accordance with results of other studies that indicated that 40 mg parecoxib twice daily ameliorated post- A B C laparoscopic pain, and attenuated the incidence of visceral and shoulder pain with a reduced requirement for analgesics following gynecological laparoscopy (29,30). In contrast to the traditional opioid drugs, parecoxib exerts its analgesic effect without opioid-induced hyperalgesia.…”
Section: A B C Discussionsupporting
confidence: 91%
“…Increasing evidence indicates that patients with cervical cancer exhibit an imbalance in the functions of Th1 and Th2 cells, with a Th2-predominant response mode (29), and the Th17/Treg balance has been noted to be disrupted in peripheral blood from patients with cervical cancer (13,32,33). In the present study, in order to improve understanding of the underlying mechanisms of postoperative immune suppression, alterations in the levels of Th1, Th2, Th17 and Treg cytokines following gynecological laparoscopy were observed in patients with cervical cancer.…”
Section: A B C Discussionmentioning
confidence: 99%
“…However, as in this study, after neuraxial opioid (spinal morphine) neither intravenous ketorolac, regular oral valdecoxib nor celecoxib are of benefit 21,24,25 . It is possible that alternative dosing regimens (for example repeated parecoxib dosing or celecoxib 400 mg BD) would have improved efficacy, given that these higher doses may be more effective for some patients 34,35 and that the pharmacokinetics of parecoxib and celecoxib in pregnancy are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…dosis berulang dapat menurunkan nyeri bahu pasca laparaskopi ginekologik sedangkan parecoxib dosis tunggal tidak dapat menurunkan angka kejadian nyeri bahu. 3 Injeksi parecoxib sama efektifnya dengan ketorolak dalam menurunkan nyeri pascabedah pada operasi laparatomi ginekologi. Penggunaan parecoxib 40 mg iv pada histerektomi total abdominal direkomendasikan sebagai sparing morfin.…”
Section: Parecoxibunclassified